If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 12x + -45 Reorder the terms: 7x = -45 + 12x Solving 7x = -45 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 7x + -12x = -45 + 12x + -12x Combine like terms: 7x + -12x = -5x -5x = -45 + 12x + -12x Combine like terms: 12x + -12x = 0 -5x = -45 + 0 -5x = -45 Divide each side by '-5'. x = 9 Simplifying x = 9
| (+15)+(-7)+(+1)= | | y=57-2 | | 2x+4x=3x+3 | | 3(x-9)=6x | | 1/5y=9-2/5y | | 4c-6=-2 | | 2n+5+4=-1 | | 4C-6=two | | xb=ya | | 2x=11+x | | 6x+1=6(x+1) | | Y=0.15x+0.55 | | 5(15+x)=-70 | | 2*5+8/2=18 | | 2.49+x= | | 9x+1/3x=0 | | 0.20(y-4)+0.16y=0.02y-0.07(60) | | 9x+3x=0 | | (4b+3b^4)-(2b-8b^4)+(5b+9b^2+6b^4)= | | 0.2m=0.3m+2.4 | | 16x^2+32x-65=0 | | m+33=112 | | -12+12=y | | 20-12=2x | | X+5x/3=24 | | 2/3(x-5)=-10+4 | | 3(m-4)+5=5m-21 | | k+37=-2(-1-4k) | | 9(4b-1)=2(9b+30) | | -x=300 | | (t+10.5)+90+2t=180 | | 4(m-4)=2(2m-8) |